2011
DOI: 10.1644/09-mamm-a-113.1
|View full text |Cite
|
Sign up to set email alerts
|

Forelimb proportions and fossorial adaptations in the scratch-digging rodentCtenomys(Caviomorpha)

Abstract: Members of the genus Ctenomys (tuco-tuco; Rodentia: Caviomorpha: Octodontidae) are considered scratch diggers. We compared the forelimbs of adult C. azarae with those of 13 species within other genera of caviomorph rodents to identify morphofunctional variation in osseous elements related to fossorial habits. Eight measurements of the humerus and ulna were used to construct five functional indices that were subjected to principal components analysis and simple comparisons among means. Ctenomys has a general mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 16 publications
(37 reference statements)
5
39
0
1
Order By: Relevance
“…Given the close haplotypic affinities within Bathyergus, it is expected that the newborns of B. suillus would also show an early development of such bone superstructures. These features are generally absent or have a later development in cursorial and semifossorial mammals . Thus, these findings support the particularity of the scratch‐digging phenotype in Bathyergus , as well as its more precocial development as compared to other mammals.…”
Section: Discussionsupporting
confidence: 72%
“…Given the close haplotypic affinities within Bathyergus, it is expected that the newborns of B. suillus would also show an early development of such bone superstructures. These features are generally absent or have a later development in cursorial and semifossorial mammals . Thus, these findings support the particularity of the scratch‐digging phenotype in Bathyergus , as well as its more precocial development as compared to other mammals.…”
Section: Discussionsupporting
confidence: 72%
“…Greater bone robustness has been linked to the requirements of body support (see regression results) during locomotion, or to the development of forces required for specific functions of the limb such as digging or food manipulation (Elissamburu & De Santis, ; Samuels et al, ; Samuels & Van Valkenburgh, ; Toledo et al, ). Thus, the robust humerus of Cyonasua (relatively high HRI value) is related to the ability to resist relatively high bending and shearing stresses, which would be associated with supporting their body mass (body mass average for Cyonasua : 19.5 kg., greater than any extant procyonid; Tarquini et al, ), as could be suggested by the low but significant positive allometry of HRI.…”
Section: Discussionmentioning
confidence: 99%
“…These scores and a lowest value for the robustness of the femur can be related with allometric changes in T. aureus , the largest species of the genus. Elissamburu and Vizcaino, (2004) and Elissamburu and De Santis (2011) analyzed the morphometric variation in other caviomorph rodents to evaluate the fossorial forms in a functional context. Comparing our results, the loadings of the indexes in Tympanoctomys are more related to cursorial forms or occasional diggers, like Dolichotis or Microcavia .…”
Section: Discussionmentioning
confidence: 99%
“…This is especially interesting and encourages the development of studies to learn more the about behavioral and structural adaptations in these families of rodents. Some authors (Elissamburu and Vizcaino 2004; Morgan and Verzi 2006; Elissamburu and De Santis 2011; Morgan and Alvarez 2013) have studied the adaptations of the forelimbs and hindlimbs, especially the digging capacity of Ctenomys , and concluded that the greater development of the medial epicondyle could be an early specialization and one of the main characters by which to recognize the digging fossorial forms. In Tympanoctomys , this feature is not observed; it can be related to the fact that this genus occurs in sandy soils then strong modifications of the limbs are not necessary.…”
Section: Discussionmentioning
confidence: 99%